Arsenic immobilization in soils amended with drinking-water treatment residuals - Sarkar, Dibyendu; Vandanapu, Vandana; Datta, Rupali K.; Makris, Konstantinos C. (My University, 2007)
Use of Fe/Al hydroxide-containing materials to remediate As-contaminated sites is based on the general notion that As adsorption in soils is primarily controlled by Fe/Al (hydr)oxides. A low-cost and potentially effective substitute for natural Fe/Al hydroxides could be the drinking-water treatment residuals (WTRs). Earlier work in our laboratory has shown that WTRs are effective sorbents for As in water. We hypothesized that land-applied WTRs would work equally well for As-contaminated soils. Results showed that WTRs significantly (p < 0.001) increased the soil As sorption capacity. All WTR loads (2.5, 5, and 10%) significantly (p < 0.001) increased the overall amount of As sorbed by both soils when compared with that of the unamended controls. The amount of As desorbed with phosphate (7500 mg kg−1 load) was ∼50%. The WTR effectiveness in increasing soil As sorption capacities was unaffected by differences in both soils' chemical properties.
Keywords: Arsenic; Pesticides; Residuals; Immobilization